2015
DOI: 10.1089/gyn.2014.0088
|View full text |Cite
|
Sign up to set email alerts
|

Adnexectomy During Vaginal Hysterectomy for Benign Indications Using Bipolar Hemostasis of Lateral Pedicles and Transvaginal Adnexa Mobilization

Abstract: Background: Using coagulation techniques to achieve hemostasis of lateral pedicles, or a fiberoptic light source to improve visibility in a narrow operating field, or transvaginal mobilization of adhered adnexa, may facilitate more salpingo-oophorectomies after vaginal hysterectomies for benign indications. Objectives: The aim of this research was to study the feasibility of adnexectomy during vaginal hysterectomy for benign indications, using bipolar coagulation to achieve hemostasis of the lateral pedicles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Purohit R et al, in his study concluded that most adnexectomies during vaginal hysterectomy for benign indications can be completed, using bipolar hemostasis and transvaginal mobilization of adhered adnexa in the pelvis. 9 To gain the access and to secure the ovarian pedicle different techniques can be employed. Conventional clamping, cutting and ligating using adnexal clamp itself is enough in most situations and minimize the pedicle slippage.…”
Section: Discussionmentioning
confidence: 99%
“…Purohit R et al, in his study concluded that most adnexectomies during vaginal hysterectomy for benign indications can be completed, using bipolar hemostasis and transvaginal mobilization of adhered adnexa in the pelvis. 9 To gain the access and to secure the ovarian pedicle different techniques can be employed. Conventional clamping, cutting and ligating using adnexal clamp itself is enough in most situations and minimize the pedicle slippage.…”
Section: Discussionmentioning
confidence: 99%
“…After vaginal hysterectomy, adhered adnexa were mobilized from the lateral pelvic wall using transvaginal mobilization of adhered adnexa from the lateral pelvic wall using tactile feel. 9 …”
Section: Methodsmentioning
confidence: 99%
“…Adhesiolysis and adnexectomy were done vaginally under vision in indicated cases. 9 Chocolate cystectomy if any, was done to preserve ovary in indicated cases. 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations